2020
DOI: 10.3389/fimmu.2020.00730
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin-1-Interleukin-17 Signaling Axis Induces Cartilage Destruction and Promotes Experimental Osteoarthritis

Abstract: Osteoarthritis (OA), which is the most common degenerative joint disorder, has been considered a non-inflammatory disease with abnormal mechanics. Interleukin (IL)-17 is a pleiotropic cytokine involved in inflammatory diseases and their production is driven by the cytokine including IL-1 and IL-23. However, little is known about the mechanism of IL-17 in the development of OA. Here, we investigated the role of IL-17 in the pathogenesis of OA using monosodium iodoacetate (MIA)-injected IL-17 and IL-1 receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 51 publications
(55 reference statements)
0
28
0
Order By: Relevance
“…IL-17 alone dose-dependently increased MMP-1, -3, -13, and MCP-1 and decreased TIMP, COL2A1, and SOX9 mRNA expression in human OA chondrocytes [ 170 ]. When IL-17 was combined with low concentrations of IL-1β, the combination increased NO production and decreased GAG synthesis in a rat patellar articular cartilage explant model greater than either cytokine treatment alone.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models Thatmentioning
confidence: 99%
“…IL-17 alone dose-dependently increased MMP-1, -3, -13, and MCP-1 and decreased TIMP, COL2A1, and SOX9 mRNA expression in human OA chondrocytes [ 170 ]. When IL-17 was combined with low concentrations of IL-1β, the combination increased NO production and decreased GAG synthesis in a rat patellar articular cartilage explant model greater than either cytokine treatment alone.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models Thatmentioning
confidence: 99%
“…IL-1β enhances nuclear factor erythroid-2 related factor 2 (Nrf2) and Heme Oxygenase-1 (HO-1) to upregulate matrix-degrading enzymes and oxidative stress [13]. IL-1β can upregulate MMP3 and MMP9 and ADAMTs by activating IL-17, thereby promoting joint inflammation and inducing chondrocyte apoptosis [14]. Ohtsuki et al [15] observed that IL-1β is also involved in upregulating Cell migration-inducing hyaluronidase 1 (CEMIP), which induces the degradation of hyaluronan in ECM.…”
Section: Resultsmentioning
confidence: 99%
“…The Von Frey test was used to measure the mechanical nociceptive threshold of mice at 0, 7, 14 and 21 days ( 19 ). Mice were placed on the test bench with a mesh bottom and adapted for 30 min.…”
Section: Methodsmentioning
confidence: 99%